Development of the forest sector in Indonesia - Sunderlin, William D. (1999)
Indonesia is among the world's leading wood products exporters, and is the leading plywood exporter. The forest sector has grown rapidly in the last three decades to 487 concessions occupying 56 million hectares. A notable change in recent years has been the rapid growth of the pulp and paper industry. The extraction of timber from concessions is over 40 million cubic metres per year whereas the government-determined threshold for sustainable production is 22 million cubic metres per year. Non-wood forest products account for 1-5% of forest sector export income. Rattan production, like that of timber, has been subject to dramatic transformation through the implementation of value-added policies and Indonesia has become the world's leading supplier of rattan furniture. The main environmental concerns related to the forest sector are: (1) deforestation and forest degradation resulting from the farming practices of agricultural smallholders; (2) deforestation and forest degradation from land use practices of large enterprises such as timber concessions, tree crop and industrial timber plantations, and pulp and paper mills; and (3) the use of fire for clearing land. The Indonesian forest industry sector is facing greater upheaval and challenges that at any point in the past 30 years. On the positive side, there may be a temporary reprieve from pressure on natural timber supplies in the short-term resulting from the decline in demand for plywood. There is no indication that current policies will provide incentives for sustainable management of natural forests. The drastic currency depreciation may lead to high demand for Indonesian forest products and the resumption of high pressures from within the forest sector. Moreover, the economic crisis has increased pressures from outside the forest sector on remaining forest resources by agriculture, mining and transmigration. Overall, the rate of exploitation of Indonesia's natural forests for industrial purposes is unsustainable.